ECOLOGY IN TEXTBOOKS: AN ANALYSIS OF ACADEMIC PRODUCTION IN BIOLOGY TEACHING AREA - Morais, Wanderson Rodrigues [UNESP]; Almeida, Maria Jose Pereira Monteiro de; Rink, Juliana (Centro Univ Nove Julho, 2022)
This paper aims to reflect on the research scenario in the field of biology teaching and textbooks, in order to understand what contributions and challenges are announced by academic productions in the area, regarding to ecology. We start from the consideration that ecology is still considered a recent science, with its concepts in constant construction and reformulation, and that basic elements of its field are influenced by society and, similarly, with regard to its teaching and presence in textbooks. Thus, we believe that the present work can contribute with a general framework that allows recognizing trends, identifying and systematizing the written production on the subject, collaborating with possible ramifications and the development of the area. Thus, we carried out a bibliographic survey in seven brazilian and two international journals, from 2001 to 2021. As a result, we identified twelve papers dealing with ecology and textbooks, from which it was possible to observe a variety of topics studied, such as: biodiversity, environment, food chain, nitrogen cycle, population flows, population ecology and ecosystem ecology. Furthermore, a third of the works point to the importance of considering historiographical aspects and the contexts of knowledge production in ecological contents, denouncing their absence and/or scarcity.
Keywords: biology textbook; academic production; ecology